Comparative docking studies of rosmarinic acid and sinesitin to inhibit HSP70 - V., Mansoureh Nazari; Mahmood, Syed; Subashini, Raman (Penerbit Universiti Malaysia Pahang, 2019)
The HSP70 family of heat shock proteins consists of molecular chaperones of approximately 70kDa in size that serve critical roles in protein homeostasis. These adenosine triphosphatases unfold misfolded or denatured proteins and can keep these proteins in an unfolded, folding-competent state. They also protect nascently translating proteins, promote the cellular or organellar transport of proteins, reduce proteotoxic protein aggregates and serve general housekeeping roles in maintaining protein homeostasis. The HSP70 family is the most conserved in evolution, and all eukaryotes contain multiple members. the HSP70 family of proteins can be thought of as a potent buffering system for cellular stress either from extrinsic (physiological, viral and environmental) or intrinsic (replicative or oncogenic) stimuli. Not surprisingly, cancer cells rely heavily on this buffering system for survival. The overwhelming majority of human tumours overexpress HSP70 family members, and expression of these proteins is typically a marker for poor prognosis.